Impact of service quality dimensions on patients’ satisfaction: a study on private hospital healthcare service in Dhaka - Haque, A. K. M. Ahasanul; Ulfy, Mohammad Arije; Hossain, Abul; Huda, Nazmul (2025)
Despite its status as a basic human right, a considerable proportion of the populace in underdeveloped countries lacks access to fundamental medical care. In the absence of a sufficient and suitable healthcare system, all other sectors of the economy would have detrimental effects. Consequently, due to the city's burgeoning population and heightened awareness of healthcare concerns, private hospitals in Dhaka are progressively providing medical services to individuals from diverse backgrounds. The objective of this research is to ascertain the factors affecting patient satisfaction with the quality of health care services in private hospitals in Dhaka City and to examine the relationship between these factors and their implementation. The SERVEQUAL framework is employed to examine the direct effects of the associated elements. In five high-traffic private hospitals in Dhaka, 230 questionnaires were distributed directly to patients, of which 226 valid responses were analyzed. This research employed SPSS 25.0, a Statistical Package for the Social Sciences, to conduct an exploratory factor analysis (EFA) with hypothesis testing. The study's findings indicate that the tangibility, reliability, responsiveness, assurance, and empathy of each factor positively and significantly influence patient satisfaction; higher t-values for these factors correspond to a stronger correlation with patient satisfaction. Thus, the favourable results of the extensive study enquiries suggest that patients exhibit more satisfaction with private healthcare services when provided with high-quality treatment. The study's findings would benefit all stakeholders, including locals, private clinics, diagnostic centres, hospital proprietors, and patients.